Tinea capitis due to Trichophyton rubrum in a negro child. - Chieco, P. (European Journal of Pediatric Dermatology, 2011)
Case report. A 3-year-old negro child presented a limited area of rarefaction and scaling on the scalp. The child attended the kindergarten, but there were no similar cases in his class and there was no history of contact with kittens. Physical examination revealed a 3 cm in diameter, roundish patch with hair rarefaction and follicular hyperkeratosis (Fig. 1); broken hairs were not visible. The fresh mycological examination highlighted 6-7 mm long hairs filled with spores (Fig. 2). Mycological cultures grew Trichophyton rubrum, granular variety (Fig. 3), leading to the diagnosis of trichophytic ringworm. After 30 days of oral therapy with griseofulvin FP 20 mg / kg / day, the scaling appearance improved and partial hair regrowth was observed (Fig. 4). The topical and oral antifungal treatment was prescribed for other 15 days.